POTENSI ANTIOKSIDAN FENOLIK DARI FAMILI MYRTACEAE DAN PERANNYA SEBAGAI BAHAN AKTIF TABIR SURYA - Suryanto, Edi (CHEMISTRY PROGRESS, 2010)
ABSTRACTSuryanto et al., 2010. The potential of phenolic antioxidant from Myrtaceae family as sunscreen active compound.The objectives of study was to determine free radical scavenging activity and measure sun protective activity of the phenolic extract in Myrtaceae family in vitro. Analyses of phytochemicals were based on total phenolic, flavonoid and condensed tannins. The antioxidant activities of extracts were determined by free radical 1.1-diphenyl-2-picrylhydrazyl (DPPH) assay. Syzygium polyanthum, clove and Eugenia aquea powder was extracted with methanol 80% at room temperature for 24 hours. Free radical scavenging activity of each extracts evaluated at 100-200 ppm level. The higher total phenolic and tannin content was find clove leave extract, followed by Eugenia aquea leave extract and Syzygium polyanthum leave extract. Contrary, Eugenia aquea leave possessed higher contents of flavonoid than clove extract and Syzygium polyanthum extract. The clove leave extract showed higher DPPH free radical scavenging than Syzygium polyanthum and Eugenia aquea leave extract at 200 ppm level. Free radical scavenging activity of three extracts increased with increasing concentration of extract. The result showed also that clove phenolic extract possessed high potential as ingredient of sunscreen followed by Eugenia aquea and Syzygium polyanthum leave phenolic extract. Result of measuring the sun protection factor (SPF) were 34.38; 33.98 and 7.92, resvectively. These result suggested that three extracts in Myrtaceae family leave having potential as antioxidant and sun protection factor (SPF) value is high that including in low protection (6-8) and medium protection (>15).Keywords : antioxidant, Myrtaceae family, phenolic extract, sunscreen